Influence of foot posture on the functioning of the windlass mechanism. (March 2017) - Lucas, Rachel; Cornwall, Mark
Highlights: What is already known The effect of the windlass mechanism in the foot is observed with extension of the first metatarsophalangeal joint. The windlass mechanism is evident in most, but not all individuals. The lack of a properly working windlass mechanism has been associated with overuse injuries of the lower extremity. What this study adds Individuals with a functioning windlass have a normal foot posture, while those without have a pronated foot posture. Individuals without a functioning windlass demonstrate more foot mobility compared to those with a functioning windlass. A non-functioning windlass mechanism may be restored by utilizing a pre-fabricated foot orthosis with medial wedging. Abstract: The absence of a functioning windlass mechanism may delay re-supination of the foot during locomotion and put excess stress on the mid-tarsal joint and soft tissues of the foot. The purpose of this study was to describe the foot posture of individuals that have an impaired or absent windlass mechanism. Forty-seven individuals (34 females and 13 males) with a mean age of 26 years were recruited to participate in this study. The Foot Posture Index was used to visually assess the posture of both feet. In addition, a digital gauge was used to measure dorsal arch height and midfoot width in bilateral resting standing. Dorsal arch height and mid-foot width were also measured in non-weight bearing. Finally, for those individuals without a functioning windlass mechanism, the amount of medial wedging needed to restore its function was measured. Subjects with an "absent" or "impaired" windlass mechanism had a mean Foot Posture Index of +6.8 (sd = 2.5) compared to +2.5 (sd = 3.1) for those with a functioning windlass mechanism. A series of independent t-tests showed that individuals without a functioning windlass mechanism had a more pronated foot posture, a lower dorsal arch height and a wider mid-foot width compared to those that had a functioning windlass mechanism. Finally, an average medial wedge of 5.1 mm (sd = 2.1) was able to produce a functioning windlass mechanism in those individuals that previously lacked one.